PENGEMBANGAN BAHAN AJAR BERBASIS KONTEKSTUAL PADA MATAKULIAH BIOLOGI UMUM - Dasrieny Pratiwi, Agil Lepiyanto (Bioedukasi Jurnal Pendidikan Biologi, 2015)
Abstract: The aim of this research is to gain contextual teaching material in in general biology class. The type of this research is developmental research or Research and Development (R&D). Developmental model which is used in this research was adapted from Sugiyono and it was limited until the step of productâs test. The result of this research shows that the quality of contextual teaching material in biology subject which is developed by the expert of teaching design, the media expert, the biology lecturer, and the students who take this subject have a valid category with the following ideality scores: 4.076, 4.09, 4.19, and 4.03. The product of contextual teaching material should be revised to gain a better result.